A Comparative Study of Factors Contributing to Reading Comprehension in L2 (English) Among Iranian and Indian Students - Mojtaba Maghsoudi; Abolfazl Khodamoradi; Seyed Hassan Talebi (Comparative Education Society of Iran ( CESIR), 2019)
Few studies have ever been conducted to find out degree of contribution of L1 reading ability and L2 general linguistic proficiency to L2 reading regarding the context of learning. Two groups of students from the Indian ESL (English as a Second Language) and Iranian English as a Foreign Language (EFL) contexts attended this study. Measures of general English proficiency (GEP), reading comprehension (RC) in L2 and reading strategy awareness (RSA) in L1 were administered among the participants. Findings showed that RSA accounted for 41% and 10% of variance in L2 RC for the Iranian and Indian groups, respectively. It was also found regression weight for RSA is still significant for the Iranian group but not for the Indian group. In addition, for the Iranian group, both RSA and GEP are significant variables in prediction of RC in L2 but for the Indian group only GEP contributed significantly to the prediction of RC in L2. In addition, for both the high and low Iranian GEP groups only the contribution of RSA was significant in the prediction of RC in L2. However, for the Indian group the role of RSA was insignificant in predicting RC in L2, for both high and low groups. As the differences of the findings are more than the similarities in the two contexts, it is suggested that reading teachers reconsider the significant role of factors that contribute more to L2 reading, regarding the moderating role that context of learning plays in this regard.